Cupric oxide film with a record hole mobility of 48.44 cm2/Vs via direct–current reactive magnetron sputtering for perovskite solar cell application. (October 2019) - Gao, Xiaoyong; Du, Yongli; Meng, Xue
Highlights: CuO film with record mobility of 48.44 cm 2 /Vs was prepared by DC magnetron sputtering. CuO can be used as HTL in perovskite solar cells. Perovskite solar cells where CuO is used as HTL layer obtained 1.3% efficiency. CuO film is best crystallized with preferential 〈−1 1 1〉 orientation at Ro/a of 1:3. The crystal lattice parameters and crystal distortion of the films were calculated. Abstract: Cupric iodide and cuprous oxide as hole–transporting layer (HTL) materials in perovskite solar cells (PSCs) have been reported. However, the compositional instability and poor electrical conductivity of films in ambient air have limited their applications in PSCs. Cupric oxide (CuO) films may be used as a HTL material in PSCs due to their high electrical conductivity and high stability in ambient air even if their hole mobility is still required to further increase. Herein, single-phase monoclinic CuO films with p –type conduction were room-temperature prepared via direct–current reactive magnetron sputtering, thereby garnering low–cost advantage. CuO film prepared at 1:3 O2 /Ar flow ratio (Ro/a ) was best crystallized and preferred 〈−1 1 1〉 oriented, thereby resulting in a record mobility of 48.44 cm 2 /Vs and small electrical resistivity of 0.50 Ω∙cm. The PSCs with CuO as HTL material obtained 1.3% power conversion efficiency, indicating that CuO films with record hole mobility could be used as a HTL material in PSCs.